Depiction of goose on the pillar of the antarala - Temples of India Project Team (Jio Institute, 2024)
A goose on the pillar (proper right) in the antarala (vestibule) of the Sitaleshwar Temple (left) and on the ceiling (right), Cave 2, Ajanta. Image source: Ghosh, A. Ajanta Murals. Delhi: Archaeological Survey of India, 1996.